THE SIGNIFICANCE OF THE SCIENCE OF SUFISM IN THE EDUCATION OF THE SOUL (Scientific journal of the Fergana State University, 2023)
Self-education is one of the most important topics. Many scholars, historians, and many books and brochures have been published on this subject. This article emphasizes the importance of Sufism in self-education.